2012
DOI: 10.5194/acp-12-8131-2012
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of submicron particles influenced by mixed biogenic and anthropogenic emissions using high-resolution aerosol mass spectrometry: results from CARES

Abstract: Abstract. An Aerodyne high resolution time-of-flight aerosol mass spectrometer (HR-ToF-AMS) was deployed during the Carbonaceous Aerosols and Radiative Effects Study (CARES) that took place in northern California in June 2010. We present results obtained at Cool (denoted as the T1 site of the project) in the foothills of the Sierra Nevada Mountains, where intense biogenic emissions are periodically mixed with urban outflow transported by daytime southwesterly winds from the Sacramento metropolitan area. During… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
205
5
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(239 citation statements)
references
References 109 publications
28
205
5
1
Order By: Relevance
“…Its O / C ratio is 0.12, confirming the nature of HOA species as being derived from primary emissions. The O / C ratio of HOA is slightly higher than 0.08 for HOA in a northern California site similarly influenced by mixed biogenic and anthropogenic emissions (Setyan et al, 2012), but lower than the values in megacities such as Mexico City and Beijing (Aiken et al, 2009;Huang et al, 2010). The HOA profile shows high similarity to other HOA mass spectra determined in Pittsburgh (R 2 = 0.91 (Ulbrich et al, 2009) and R 2 = 0.84 (Zhang et al, 2005a)) and also the averaged HOA spectra on a global scale (R 2 = 0.88; Ng et al, 2010) (Fig.…”
Section: Hydrocarbon-like Oa Factormentioning
confidence: 98%
See 1 more Smart Citation
“…Its O / C ratio is 0.12, confirming the nature of HOA species as being derived from primary emissions. The O / C ratio of HOA is slightly higher than 0.08 for HOA in a northern California site similarly influenced by mixed biogenic and anthropogenic emissions (Setyan et al, 2012), but lower than the values in megacities such as Mexico City and Beijing (Aiken et al, 2009;Huang et al, 2010). The HOA profile shows high similarity to other HOA mass spectra determined in Pittsburgh (R 2 = 0.91 (Ulbrich et al, 2009) and R 2 = 0.84 (Zhang et al, 2005a)) and also the averaged HOA spectra on a global scale (R 2 = 0.88; Ng et al, 2010) (Fig.…”
Section: Hydrocarbon-like Oa Factormentioning
confidence: 98%
“…Urban emissions from Kuopio can also be another important contributor to the observed high levels of OOA. Setyan et al (2012) characterized the properties of atmospheric aerosol in a mixed biogenic and anthropogenic emission area. They observed that more oxidized OOA originates from biogenic VOCs, whereas less oxidized OOA is sourced to urban emission photooxidation products.…”
Section: Oxygenated Oa Factorsmentioning
confidence: 99%
“…Fine particle size distribution: the SMPS used at T1 is a similar design described in Setyan et al (2012) and it measured low RH particle sizes from 10 to 858 nm. The SMPS data were corrected to take into account the DMA transfer function, the bipolar charge distribution, the CPC efficiency and the internal diffusion losses (Setyan et al, 2014).…”
Section: Instruments Used At the T1 Site (Evergreen Schoolmentioning
confidence: 99%
“…During the CARES campaign near Sacramento, CA, aircraft observations showed that Δorg/ΔCO measurements were 35-44 μg/m 3 ppmv -1 when anthropogenic emissions evolved in the absence of strong biogenic emissions and 77-157 μg/m 3 ppmv -1 when the urban plume interacted with regions of strong biogenic emissions (Shilling et al, 2013). Measurements from a ground site during CARES report average Δorg/ΔCO values of 36 μg/m 3 ppmv -1 in the Sacramento plume during periods of low biogenic emissions and 97 μg/m 3 ppmv -1 during periods of high biogenic emissions (Setyan et al, 2012). Several additional 20 field studies report enhancements of SOA through interactions of anthropogenic and biogenic interactions, but may not employ the Δorg/ΔCO metric (Zhou et al, 2016;Xu et al, 2015;Ng et al, 2017;Bean et al, 2016).…”
Section: Introduction 10mentioning
confidence: 99%
“…Chem. Kleinman et al, 2008), to 100 μg/m 3 ppmv -1 in the Po Valley, Italy (Crosier et al, 2007), to 44 -197 μg/m 3 ppmv -1 in Sacramento, CA (Shilling et al, 2013;Setyan et al, 2012), to 97-133 μg/m 3 ppmv -1 in Paris (Freney et al, 2014). The same studies have found that Δorg/ΔCO increases roughly linearly with airmass age for the first 1 day of aging and levels off after approximately 2 days (de Gouw and Jimenez, 2009;DeCarlo et al, 2010;Kleinman et al, 2008;Takegawa et al, 2006;Sullivan et al, 2006;Freney et al, 2014).…”
Section: Introduction 10mentioning
confidence: 99%